Electrical stimulation of microengineered skeletal muscle tissue: Effect of stimulus parameters on myotube contractility and maturation - Banan Sadeghian, Ramin; Ebrahimi, Majid; Salehi, Sahar (Journal of tissue engineering and regenerative medicine, 2018)
Skeletal muscle tissues engineered in vitro are aneural, are short in the number of fibres required to function properly and degenerate rapidly. Electrical stimulation has been widely used to compensate for such a lack of neural activity, yet the relationship between the stimulation parameters and the tissue response is subject to debate. Here we studied the effect of overnight electrical stimulation (training) on the contractility and maturity of aligned C2C12 myotubes developed on micropatterned gelatin methacryloyl (GelMA) substrates. Bipolar rectangular pulse (BRP) trains with frequency, half-duration and applied pulse train amplitudes of f = 1 Hz, t = 0.5 ms and V = {3 V, 4 V, 4.5 V}, respectively, were applied for 12 h to the myotubes formed on the microgrooved substrates. Aligned myotubes were contracting throughout the training period for V ≥ 4 V. Immediately after training, the samples were subjected to series of BRPs with 2 ≤ V ≤ 5 V and 0.2 ≤ t ≤ 0.9 ms, during which myotube contraction dynamics were recorded. Analysis of post-training contraction revealed that only the myotubes trained at V = 4 V displayed consistent and repeatable contraction profiles, showing the dynamics of myotube contractility as a function of triggering pulse voltage and current amplitudes, duration and imposed electrical energy. In addition, myotubes trained at V = 4 V displayed amplified expression levels of genes pertinent to sarcomere development correlated with myotube maturation. Our findings are imperative for a better understanding of the influence of electrical pulses on the maturation of microengineered myotubes.